Perbandingan Pengaruh Latihan Ball Standing Throw dengan Ball 3 Straide Rhytem and Throw Terhadap Peningkatan Power Lengan - Falah, Ariq Badrul; Maryati, Sri; Sugiawardana, Ruli (Jurnal Keolahragaan, 2024)
ABSTRACTThis research aims to determine whether there are positive changes in arm power as a result of the Ball Standing Throw treatment with Ball 3 Straide Rhytem and Throw. The research method used is pre-experimental design. The research location is at SMK YPS 1 Ciamis Regency. The research subjects were 10 sons. The sampling technique is total sampling. Based on data analysis using SPSS series 26, the results of data processing consist of: 1. Ball standing throw training has a significant influence on increasing arm power. 2. 3 straide rhythm and throw ball training has a significant influence on increasing arm power. 3. There is a significant difference between ball standing throw training and ball 3 straide rhythm and throw training in increasing arm power. Conclusion: Standing ball throw training with 3 straide rhythm and throw ball training increases arm power.ABSTRAKPenelitian ini bertujuan untuk mengetahui adanya perubahan secara positif pada power lengan dari hasil perlakuan Ball Standing Throw  dengan Ball 3 Straide Rhytem and Throw. Metode penelitian yang digunakan adalah pre-experimental design. Lokasi penelitian di SMK YPS 1 Kabupaten Ciamis. Subjek penelitian yaitu 10 orang putra. Teknik pengambilan sampel yaitu total sampling. Berdasarkan analisis data menggunakan SPSS serie 26, hasil pengolahan data terdiri dari: 1. Latihan ball standing throw memberikan pengaruh yang signifikan terhadap peningkatan power lengan. 2. Latihan ball 3 straide rhytem and throw memberikan pengaruh yang signifikan terhadap peningkatan power lengan. 3. Terdapat  perbedaan  yang   signifikan  antara  latihan ball standing throw dengan latihan ball 3 straide rhytem and throw terhadap peningkatan power lengan. Kesimpulan: Latihan ball standing throw dengan latihan ball 3 straide rhytem and throw terhadap peningkatan power lengan